In Vivo Kinematics for Various Robotically Performed Total Knee Arthroplasty Implant Designs - Ong, Michael Tim‐Yun; LaCour, Michael T.; Yung, Patrick Shu‐Hang; Dessinger, Garett M.; Komistek, Richard D. (Journal of orthopaedic research, 2025)
ABSTRACT Although it is well‐documented that robotic‐assisted total knee arthroplasty (TKA) can improve surgical precision, evaluations of the postoperative kinematics of patients implanted using robotics remain less common. The objective of this study is to analyze the weight‐bearing kinematics for multiple TKAs implanted using two different surgical robots. In vivo knee kinematics were assessed using fluoroscopy for 28 subjects implanted with a Bi‐Cruciate Stabilized (BCS) TKA, 23 with a Bi‐Cruciate Retaining (BCR) TKA, 13 with a posterior stabilized (PS) TKA, and 22 with a cruciate retaining (CR) TKA. All subjects were implanted by the same surgeon using the respective company's surgical robot. All subjects performed a weight‐bearing deep knee bend. Parameters of interest include the femoral condylar anterior/posterior motion, femorotibial axial rotation, and weight‐bearing range‐of‐motion. The BCS TKA experienced the most posterior rollback, 13.4 ± 4.4 mm for the lateral condyle and 5.8 ± 2.5 mm for the medial condyle. These subjects also experienced the most femorotibial axial rotation, +9.3 ± 5.3°. Conversely, CR subjects experienced the least overall rollback and most anterior sliding, 0.4 ± 3.8 mm of lateral rollback and 1.9 ± 4.1 mm of medial anterior sliding. Implant design appears to play a significant role in postoperative kinematics. Improved stability is evident in TKAs that account for the ACL. However, no system behaved significantly better nor worse than previously published literature evaluating standard instrumentation. Level of Evidence: Level 3, retrospective cohort study.